Gerontocracy in Motion? - European Cross-Country Evidence on the Labor Market Consequences of Population Ageing - Michael Fertig; Christoph M. Schmidt (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2003)
Taking a European cross-country perspective, this paper addresses the most important issues in the nexus of population ageing and labor markets.We start from a descriptive overview of the demographic change currently shaping European societies.The subsequent section intensively discusses the potential consequences of these demographic processes for and interdependencies with the labor market situation in Europe.We place particular emphasis on the issue of non-competitive wage setting. In our empirical application we demonstrate that moderately large birth cohorts seem to experience lower employment rates, but also that education investments might be able to mitigate these consequences, and that the relative economic success of large cohorts might even be disproportionately positive. Finally, in the concluding section we review possible policy options for coping with the consequences of population ageing.
Keywords: J11; J21; 330; Demographic change; cohort size; unemployment; Arbeitsmarkt; Alternde Bevölkerung; Lohnpolitik; Kohortenanalyse; Arbeitslosigkeit; Vergleich; Europa